2008
DOI: 10.1063/1.2884329
|View full text |Cite
|
Sign up to set email alerts
|

Control of spontaneous emission coupling factor β in fiber-coupled microsphere resonators

Abstract: The spontaneous emission coupling factor ␤ is studied for fiber-coupled microspheres with a thin gain layer of phosphorus codoped sol-gel erbium silica-aluminum glass. From the input-output characteristics of the lasing, ␤ = 0.039 is estimated for a sample with a gain layer on the sphere surface. ␤ is estimated to increase to 0.19 when an additional silica glass thin layer is overcoated to improve the overlap between the gain layer and the optical mode of the lasing inside the sphere. [4][5][6][7][8][9] In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…4a and b). Much of the work being done on WGM microcavities has been to achieve the ultimate quality factors [45,46] required for investigations of cavity quantum electrodynamics [23], quantum informatics applications [47][48][49] and nonlinear optics [50,51] in a regime of strong coupling. The typical value of Q-factor for composite CdTe QDs/microcavity of 3 µm size is $ 3500, which corresponds to the value of average photon storage time $ 1 ps.…”
Section: Spherical Microcavities As Photonic Atomsmentioning
confidence: 99%
“…4a and b). Much of the work being done on WGM microcavities has been to achieve the ultimate quality factors [45,46] required for investigations of cavity quantum electrodynamics [23], quantum informatics applications [47][48][49] and nonlinear optics [50,51] in a regime of strong coupling. The typical value of Q-factor for composite CdTe QDs/microcavity of 3 µm size is $ 3500, which corresponds to the value of average photon storage time $ 1 ps.…”
Section: Spherical Microcavities As Photonic Atomsmentioning
confidence: 99%
“…For example, Yang and Vahala [25] used the sol-gel method to cover the surface of SiO 2 microspheres with a 1-μm thick erbium-doped layer from which 1530-nm lasing was observed with a threshold of 26 μW. Recently, Takashima et al [84] showed that by overcoating the sol gel layer with a layer of SiO 2 to a total thickness of 200 nm the coupling coefficient of the lasing emission into selected WGM can be increased from 0.039 to 0. old of 65 nW at 1050 nm was observed from a SiO 2 sphere coated with neodymium-doped gadolinium oxide nanocrystals [85]. In another novel approach, a SiO 2 microsphere was coated with a layer of erbium-doped phosphate glass.…”
Section: Active Microspheres For Microlasersmentioning
confidence: 99%
“…Weak fluorescence of Rh6G still remained, since the energy transfer efficiency is not 100%. The dependence of a lasing threshold on donor-acceptor concentrations can be quantified via a spontaneous emission coupling ratio β (Horowicz et al, 1992;Takashima et al, 2008). To determine the β value, defined as the fraction of spontaneous emission coupled into a lasing mode with respect to the spontaneous emission into all modes, the input-output power relationship was modeled using a rate equation (Yokoyama and Brorson, 1989;Kippenberg et al, 2006):…”
Section: Förster Energy Transfermentioning
confidence: 99%